2014
DOI: 10.3109/00365548.2013.866269
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated cryptococcosis, invasive aspergillosis, and mucormycosis in a patient treated with alemtuzumab for chronic lymphocytic leukaemia

Abstract: We report the case of a 42-y-old man treated with alemtuzumab for chronic lymphocytic leukaemia, who developed 3 successive deep fungal infections. Despite being treated with liposomal amphotericin B and 5-flucytosine for disseminated cryptococcosis, he developed pulmonary invasive aspergillosis, followed by pulmonary mucormycosis. Several deep fungal infections may occur in association in an immunocompromised host after treatment with alemtuzumab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The first reports of cryptococcal infection complicating cancer date back to the 1920s and 1930s, and by the 1940s a prominent association with Hodgkin lymphoma (HL) was recognised . Some authors have suggested that recent use of more dose‐intense and lymphocyte‐depleting chemotherapeutic regimens, such as, rituximab, alemtuzumab, fludarabine, cyclophosphamide and prolonged corticosteroids further elevate the risk of cryptococcal disease in patients with malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…The first reports of cryptococcal infection complicating cancer date back to the 1920s and 1930s, and by the 1940s a prominent association with Hodgkin lymphoma (HL) was recognised . Some authors have suggested that recent use of more dose‐intense and lymphocyte‐depleting chemotherapeutic regimens, such as, rituximab, alemtuzumab, fludarabine, cyclophosphamide and prolonged corticosteroids further elevate the risk of cryptococcal disease in patients with malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…50 and appropriate monitoring and/or prophylaxis up to 180 days posttreatment have been proven helpful in limiting IFIs. 87,102,[104][105][106] In addition to the cited cohort studies, several additional case reports of IFIs in adults under anti-CD52 treatment are reported, including (i) aspergillosis, [107][108][109][110] (ii) cryptococcosis, 109,[111][112][113][114] (iii) PJP, 115 (iv) mucormycosis, 109 (v) blastomycosis, 116 T cells and abnormal cytotoxic T-cell-specific responses. 124,126 The presently available data suggest a subtle increase in the risk of infection in association with rituximab.…”
Section: Ctla-4 Fusion Proteinsmentioning
confidence: 99%
“…In addition to the cited cohort studies, several additional case reports of IFIs in adults under anti‐CD52 treatment are reported, including (i) aspergillosis, (ii) cryptococcosis, (iii) PJP, (iv) mucormycosis, (v) blastomycosis, (vi) histoplasmosis, (vii) fusariosis and (viii) microsporidiosis . A case of “fungal oesophagitis” due to alemtuzumab was also identified …”
Section: Induction Of Lymphopeniamentioning
confidence: 99%
“…Patients with chronic lymphocytic leukaemia (CLL) frequently present with pulmonary injuries (Khanijo et al , ), such as infections that include bacterial and pneumocystis pneumonia or invasive aspergillosis (Henn et al , ). Lungs may also be the site of leukaemic pulmonary infiltration – an extra‐nodal development of the disease – in the pulmonary parenchyma (Hill et al , ; Carmier et al , ).…”
Section: Key Features From 19 Patients Presenting With Symptomatic Brmentioning
confidence: 99%